Estrategias motivacionales para incrementar el interés por la asignatura de estudios sociales en los estudiantes de los novenos años de la sección vespertina del Instituto Tecnológico Superior Huaquillas, del cantón Huaquillas, El Oro, año 2013. - Hidalgo Alcivar, Rosa Maribel (2015)
This research points out the main characteristics of the problems that are involved in education , from the scientific research methods was determined that within the due educational process exists and the following problem remains: How to increase interest the subject of social studies students from the ninth year of the afternoon section of the top technological institute Huaquillas , the canton Huaquillas , El Oro, academic year 2013 ?. What the proposed topic today is expressed as actions on how to develop motivational strategies to increase interest in the subject of social studies students in years ninths , seeking to generate an attitudinal change in students that aims to solve and improve the process teaching and learning .